The Correlation between Self Efficacy with Problem Solving Ability of Student in Studying Ecosystem - Rasyidina, Sumayya Ainur; Suharsono, Suharsono; Meylani, Vita (Universitas Islam Negeri Walisongo Semarang, 2023)
Students need the ability to explore, think critically and analyze a problem for a logical and appropriate solution. Problem solving abilities accompanied with a belief in their abilities (self efficacy) will maximize student abilities in and get maximum grades. This research aims to analyze the correlation between self efficacy and students' problem-solving abilities in ecosystem material. The method used is a quantitative method with a correlational approach (relationship study). The data collection technique was in the form of a problem-solving ability test in the form of an essay about ecosystem and a self efficacy questionnaire. The data analysis technique uses the Product Moment correlation test. Based on the results of data analysis and hypothesis testing, a correlation coefficient value of 0.675 was obtained, which means that the correlation coefficient level is strong. It can be concluded that there is a correlation between self efficacy and problem-solving abilities of students in ecosystem material with a strong correlation coefficient.